Robot-assisted laparoscopic nephroureterectomy for urothelial carcinoma with inferior vena cava incision and repair - Knight, Richard B (J Surg Case Rep, 2019)
Locally advanced urothelial carcinoma of the renal collecting system presents a unique challenge to the urologist performing nephroureterectomy, particularly if the tumor invades the renal vein or the IVC. Preoperative planning and a multidisciplinary approach are important to optimize the outcomes for these patients. The use of robotic assistance for laparoscopic nephroureterectomy has become common, but a simultaneous robotic assisted IVC excision has yet to be reported. This case report describes a robotic assisted laparoscopic right nephroureterectomy with IVC resection and retroperitoneal lymphadenectomy for locally advanced urothelial carcinoma. For a patient with locally advanced urothelial carcinoma of the renal collecting system which obliterates the renal vein, robotic assisted surgery provides a minimally invasive alternative to open surgery.